STUDI PENCIPTAAN MULTIMEDIA KERIS DENGAN KONSEP ANIMASI EDUKASI - Rahman, Anung (Institut Seni Indoensia Surakarta, 2010)
The multimedia applicatiton, its aesthetic, and its contents are threechotomy which is inherent to theÂ interractive education planning. All of these must be have an equal function if a developer wish to have anÂ optimal results to the education process. This research will explore the keris as a multimedia materialapplied to the education process. This also contains an applied creation which is combine between kerisÂ education 's contents and an aesthetic of multimediaa material. The creation of â€œkeris multimedia material